Framing Media Merekam Feminisme Indonesia - Pratiwi Utami (Jurnal Komunikasi, 2010)
This article explains the framing of feminism in Indonesian newspaper. As an example, a research on how Indonesian feminism was framed in KOMPAS Daily from year 1997-1999 will be included. KOMPAS had been chosen as the research object because this newspaper publishes news about gender and women movement periodically. The discussion in this research will range from textual analysis to the production of news about feminism in media newsroom. Through this article, we also could observe how media ethically should respond the sensitive issues. Because in any situation, media ought to always tell the truth, in order to protect the fundamental rights of the society.